2004
DOI: 10.1158/1078-0432.ccr-03-0340
|View full text |Cite
|
Sign up to set email alerts
|

Improved Targeting of Pancreatic Cancer

Abstract: Purpose:The early detection and diagnosis of pancreatic cancer remains a major clinical challenge in which imaging procedures have a central role. The purpose of this study was to evaluate a pretargeting method with a bispecific PAM4 (bsPAM4; anti-MUC1) antibody for radioimmunoscintigraphy of experimental human pancreatic cancer.Experimental Design: A bispecific F(ab) 2 antibody was generated from chimeric PAM4 Fab and murine 734 (antiindium-diethylenetriaminepentaacetic acid) Fab fragments and then used in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…19). Higher levels of TF10 in the blood would lead to unacceptably high binding of the radiolabeled peptide within the blood (i.e., low tumor/blood ratios), whereas administering the peptide at a later time would mean the concentration of TF10 in the tumor would be decreased with consequently reduced concentration of radiolabeled peptide within the tumor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19). Higher levels of TF10 in the blood would lead to unacceptably high binding of the radiolabeled peptide within the blood (i.e., low tumor/blood ratios), whereas administering the peptide at a later time would mean the concentration of TF10 in the tumor would be decreased with consequently reduced concentration of radiolabeled peptide within the tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Production of DOTA-conjugated hPAM4, whole-IgG, has been described (7). In vitro characterization of the TF10, along with PAM4-IgG and other PAM4-based constructs, was conducted by enzyme immunoassay (4), SDS-PAGE (17), high-performance liquid chromatography (19), and lowpressure size-exclusion column chromatography (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…131,132 PRIT approaches with PAM4, using a bivalent and, subsequently, a trivalent bispecific antibody that binds the HSG hapten (TF10), have recently demonstrated improved imaging abilities relative to conventional RIT. 133,134 The latter showed an approximately 200-fold improved tumor-to-blood ratio when compared with directly labeled PAM4 IgG antibody. 134 Given the flexibility of the HSG hapten, this system could be modified for therapeutic purposes, and radiation dose estimates suggested that PRIT with 90 Y-labeled TF10 would provide a greater antitumor effect than 90 Y-labeled PAM4.…”
Section: Figmentioning
confidence: 98%
“…We have examined bsMAb that can localize other tumor-associated antigens, such as colon-specific antigen-p (78), a MUC-1 antigen that is highly specific for pancreatic cancer (82), and CD20 for targeting non -Hodgkin's lymphoma (83). Studies have been initiated to examine the capability of an anti-CD20 Â anti-HSG bsMAb, prepared by the dock-and-lock method (63), to localize human lymphoma cells in SCID mice.…”
Section: Can Pretargeting Provide a New Paradigm For Antibody-based Mmentioning
confidence: 99%